Understanding Processes of Peer Clique Influence in Late Childhood and Early Adolescence. (14th August 2017) - Ellis, Wendy E.; Zarbatany, Lynne
Abstract: Cliques, or groups of peers who interact frequently, are a key social context during childhood and adolescence, providing safety and preferential access to resources. Membership in cliques influences behavior and adjustment, but little is known about the processes by which these influences occur. In this article, we identify putative self and clique socialization processes that may account for greater similarity among clique members over time. Greater adherence to clique norms occurs when members are uncertain about their membership or have limited access to valued clique resources, and when cliques control more resources and are more cohesive. We speculate about other clique influence processes, including those that support children's attempts to distinguish themselves from cliquemates. Understanding clique influence processes can inform efforts to help children and youth resist the negative influences of cliques while protecting the benefits of membership.